Competitiveness, investment and efficiency analysis of edible bird’s nest ranching in Johor Bahru and Gua Musang, Malaysia - Ya'acob, Fatin Farazh (2019)
The swiftlet industry is listed under 12 Entry Point Projects (EPP) under the Agriculture NKEA which is one of the cores of Economic Transformation Programme (ETP) as it can generate income for the nation. Malaysia aims to dominate at least 40 percent of global demand for EBN by year 2020. Yet Malaysia was only able to meet 20 percent of world export. Although these swiftlet ranching are located in both urban and rural areas but a majority are in the earlier. Previous literatures have suggested that Malaysian swiftlet ranching is less competitive than that in Indonesia and Thailand. It lacks strategic plans to enhance its competitiveness with a dearth of research on its competitiveness. Yet the number of swiftlet houses is increasing annually. Even though this industry is lucrative, but it is high risk and unpredictable. To raise profit, ranchers need sufficient knowledge on efficient swiftlet house management particularly on how to fully utilize inputs to maximize the EBN production. The structure of swiftlet ranching between urban and rural area differs and a question arises whether this could affect the production of EBN. This study has been conducted in Johor Bahru and Gua Musang with the earlier and latter representing swiftlet ranching activities in urban and rural areas respectively. Therefore, this study has three aims: (i) to assess the factors that contribute to or lack of competitiveness of swiftlet ranching, (ii) to determine factors that influence investors’ decision making in swiftlet ranching activities and (iii) to assess the level of efficiency of switflet houses and pinpoint the best operating practices of efficient ranchers in both Johor Bahru and Gua Musang. For the first objective, a survey of 95 swiftlet ranchers from each of the two districts was undertaken to assess the factors that contribute to the competitiveness for both area. The Porter Diamond’s model of competitiveness is applied using factor analysis. For the second objective, the same respondents were used to examine the factors influencing investment decision making. The Investor Behaviour theory is adopted as the analytical model using PLS-SEM methods. For objective three, the theory of Frontier Efficiency and non-parametric Data Envelopment Analysis (DEA) method were used to measure the efficiency of swiftlet houses. For this third objective, a 150 swiftlet houses is surveyed each for Gua Musang and Johor Bahru. For objective one, it was found that factor conditions is the most important component followed by demand conditions, firm strategy and structure and rivalry, related and supporting industry, role of government and finally chance for both areas. Knowledge and experience are most important factor to be competitive and to be successful in swiftlet ranching industry. For objective two the result revealed that in Johor Bahru, heuristic construct has the highest impact to investment decision making followed by market and herding constructs for Johor Bahru. Meanwhile for Gua Musang, market construct has the highest impact to investment decision making followed by heuristic and herding. The prospect construct was revealed to be not significant for both districts. Potential investors have to consider various factors carefully before making investment decisions. For objective three, the result highlights the existence of scale inefficiency among swiftlet houses in Johor Bahru and Gua Musang. The swiftlet houses are too small and did not benefit from economies of scale. This industry has to develop standard operating procedures regarding the right formula of swiftlet house practices to attract the swiftlet into entering and producing good quality nests. Reliable data sharing from efficient ranchers can be used to raise the efficiencies of Malaysian swiftlet houses. The major limitation of this study is on the total number of respondents selected. Due to difficulties to obtain willing respondents, a total of 190 ranchers and 300 swiftlet houses were surveyed for both districts. The sample sizes could be expanded by incorporating other players such as value adding EBN processors and EBN exporters. In this manner, the study could also be further improved by expanding the investigations all along the value chain. By adopting this approach, more information could be gathered, analysed and the findings on efficient practices of value adding EBN processing and exporting disseminated.